Differences between kayakers and healthy controls in stabilizing functions of the trunk - Voglar, M.; Sarabon, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Anticipatory postural adjustments (APAs) are typically initiated before voluntary movements and/or expected external perturbation while unexpected postural perturbation elicits postural reflex reactions (PRRs). Both APAs and PRRs are important components in the control of spinal stability that can be modified by training (Pedersen et al 2007). In kayaking good spinal control and balance are required that could potentially result in adaptations of stabilizing functions of the trunk. Therefore the aim of present study was to investigate if athletes trained in wild waters kayaking represent different spinal control than healthy control subjects. We hypothesized that kayaking trained individuals will represent earlier APAs and shorter PRRs than healthy controls. Methods Sixteen kayakers (4 W, 21.0 ± 4.0 years, 174.7 ± 8.9 cm, 70.6 ± 10.6 kg) and 12 healthy controls (4 W, 23.4 ± 3.5 years, 179.7 ± 9.0 cm, 73.8 ± 13.7 kg) without spinal or neurological disorders participated in the present study. In measurements of APAs participants performed fast voluntary arm raises on a self-selected timing after visual clue. In measurements of PRRs the participants were standing with elbows flex at 90° when the load (7 kg) was suddenly released in random timing (5 to15 s) onto their hands. The instruction was to stop the load as quick as possible. In both tests 20 repetitions were performed and surface electromyography was used for recording activation of the following muscles: multifidus, erector spinae, obliques internus and externus abdominis. Results There were no statistically significant differences between the two groups of subjects as concerns APAs (p > 0.05). Only obliques externus showed a moderate tendency, however, not reaching the level of statistical significance (t = 1.85, p = 0.07, ES = 0.12). In the sudden loading test the reflex latency of two muscles were statistically significantly shorter in the group of kayakers (multifidus: t = 1.96, p < 0.05, ES = 0.16 and obliques internus: t = 2.32, p < 0.05, ES = 0.20), however, no differences were found in the other two muscles (p > 0.05). Discussion Results confirmed our hypothesis that kayakers have more efficient postural control presented as shorter PRRs of some trunk muscles but in contrast we found no effects on APAs. Results are also in agreement with findings from Pedersen et al (2007) who suggested that PRRs can be trained. Further research of seated balance training effects on sport performance and also on spine stability in terms of prevention and rehabilitation of low back pain is needed.